Econometric methods and their applications in finance, macro and related fields - Hadri, Kaddour; Mikhail, William (World Scientific Company, 2014)
Explores the concept of supply ecosystems, emphasizing the interconnection and interdependence of operations, supply, and contract management. Integrates perspectives from logistics, technology, and quality management to show how cooperation across supply networks creates strategic advantage in global business environments.